2016
DOI: 10.1051/0004-6361/201527836
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): Improved emission lines measurements in four representative samples at 0.07 <z< 0.3

Abstract: This paper presents a new catalog of emission lines based on the GAMA II data for galaxies between 0.07 < z < 0.34. The catalog includes four subsamples containing 3000 galaxies drawn from the GAMA II survey and spanning four redshift windows. The four samples are representative of intermediate-mass galaxies down to log M * > 9.4 at z ∼ 0.1 and log M * > 10.6 at z ∼ 0.30. We have developed a dedicated code called MARVIN that automates the main steps of the data analysis, but imposes visual individual quality c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…This fraction grows with decreasing stellar mass, until we reach the completeness limit (∼ 10 9 M ). This behavior is consistent with previous results (e.g., Hammer et al 1997, Rodrigues et al 2016and Sobral et al 2011. Comparing with Figure 4 in Sobral et al (2011), we find that the slope of the relation is compatible, despite the different mass range and redshift.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This fraction grows with decreasing stellar mass, until we reach the completeness limit (∼ 10 9 M ). This behavior is consistent with previous results (e.g., Hammer et al 1997, Rodrigues et al 2016and Sobral et al 2011. Comparing with Figure 4 in Sobral et al (2011), we find that the slope of the relation is compatible, despite the different mass range and redshift.…”
Section: Resultssupporting
confidence: 93%
“…Their work was based on a low-resolution spectroscopic survey, dealing with more massive galaxies, but with a lower EW detection limit than us (15 Å in the OII[3727] line). More recently, Rodrigues et al (2016) found a higher fraction (∼ 45%), dealing also with massive galaxies (∼ 10 10 M ) and with a much lower EW limit (10 Å in the Hα line).…”
Section: Gas Phase Propertiesmentioning
confidence: 96%
“…which contain at least 300 tracer particles in our HR (SR) test set. This value corresponds roughly to the typical host mass of emission line galaxies (ELGs, see e.g., Rodrigues et al 2016). We specify this mass threshold as a sufficiently resolved halo in our HR (SR) set.…”
Section: Mock Halo Catalog Analysismentioning
confidence: 99%